Segmental Renal Ischemia following Transplantation of Horseshoe Kidney as Separate Allografts - J. T. Foster; P. E. Morrissey (Case Reports in Transplantation)
Introduction. Horseshoe kidney is a congenital anomaly that presents unique challenges for the transplant surgeon. The mere presence of horseshoe kidney should not preclude consideration for transplantation. Case Report. A 33-year-old women suffering from end-stage renal disease underwent deceased donor renal transplant with a divided horseshoe kidney. We present a postoperative complication and the technical strategy for transplant salvage. The patient currently has excellent graft function. Discussion. Horseshoe kidneys do present challenges for successful transplantation. Though case reports of successful transplantation are increasing, we present a technical complication and successful transplant salvage strategy. Technical descriptions in the literature of successful back-table preparation strategies should help more transplant surgeons to begin to utilize this resource. Conclusion. This study concludes that horseshoe kidneys can be successfully used for transplantation and provides a technical strategy to salvage the transplant after a unique complication associated with these donor kidneys.